2016
DOI: 10.1136/jech-2016-207583
|View full text |Cite
|
Sign up to set email alerts
|

School and seasonality in youth suicide: evidence from Japan

Abstract: Our findings strongly indicate that the cyclical pattern of youth suicide is closely related to the school calendar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…The increase in student suicides during the summer break identified in this study was notable because the summer is typically characterized by a decline in suicide deaths among students (Matsubayashi et al, 2016). Our surveys did not contain many student respondents, but the results indicate that their mental health condition was worse than most of the other occupation categories (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The increase in student suicides during the summer break identified in this study was notable because the summer is typically characterized by a decline in suicide deaths among students (Matsubayashi et al, 2016). Our surveys did not contain many student respondents, but the results indicate that their mental health condition was worse than most of the other occupation categories (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, a survey conducted between June and July (after school reopening) by the National Center for Child Health and Development reported that 72% of surveyed students (age 7-17 years) reported symptoms that indicated some form of stress reactions (National Center for Child Health and Development 2020). Returning to school after a summer break is known to be difficult for some students even in normal years, and student suicides have previously peaked on the first day of school after the summer break, specifically on September 1st (Matsubayashi et al, 2016). Many schools reopened in August this year because of the shortened school days in the spring, and thus the peak may have shifted earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies argue that schooling substantially contributes to the high stress prevalence and stress-related mental health problems. For example, youth suicide rates increase at the beginning of the school year (Lahti et al, 2005;Matsubayashi et al, 2016) and, generally, are higher while school is in session (Hansen and Lang, 2011). Further, there is evidence that academic stress increases suicidal ideation (Ang and Huan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies argue that schooling substantially contributes to the high stress prevalence and stress-related mental health problems. For example, youth suicide rates increase at the beginning of the school year (Lahti et al, 2005;Matsubayashi et al, 2016) and, generally, are higher while school is in session (Hansen and Lang, 2011). Further, there is evidence that academic stress increases suicidal ideation (Ang and Huan, 2006).…”
Section: Introductionmentioning
confidence: 99%